THE ROLE OF MAINTENANCE THERAPY IN COMPLEX TREATMENT OF CHRONIC GENERALIZED PERIODONTITIS IN PATIENTS WITH IRON DEFICIENCY ANEMIA - I. A. Slavinsky; L. A. Skorikova; N. P. Bychkova (Кубанский научный медицинский вестник, 2016)
Periodontitis - is a multifactorial disease of the tooth supporting-holding unit caused by microbial plaque. In patients with chronic generalized periodontitis in conjunction with iron deficiency anemia standard dental treatment is not effective in most cases. To achieve long-term and stable remission in these patients can only be combined comprehensive periodontal treatment, including subsequent maintenance therapy, and treatment of iron deficiency anemia. Dispensary observation of patients should be carried out at least 1 time in 3 months with control of basic periodontal indices and the correction level of oral hygiene. In some cases, it is recommended to reduce the interval between visits.